Charge transport and contact resistance in coplanar devices based on colloidal polyaniline dispersion. Issue 17 (8th May 2016) - Masillamani, Appan Merari; Peřinka, Nikola; Hajná, Milena; Stejskal, Jaroslav; Tondelier, Denis; Bonnassieux, Yvan; Vanel, Jean‐Charles; Geffroy, Bernard; Mencaraglia, Denis
ABSTRACT: The charge transport properties of thin films prepared from colloidal dispersion of polyaniline stabilized by poly( N ‐vinylpyrrolidone) (PANI/PVP) have been investigated. The electrical characterization of coplanar device comprising of gold electrodes and PANI/PVP film deposited by spin coating served to gain insights into the contact and bulk resistance. The films prepared from PANI/PVP colloidal dispersion show high stability over a large temperature range. Temperature dependent measurements in the range from 90 to 350 K reveal that the charge transport can be described by a three‐dimensional variable‐range hopping mechanism as the dominant mode in the films. The stability of the films cast from dispersion within a large temperature range opens the possibility of the application as a polymer semiconductor layer in sensors and charge‐transport interlayer in organic solar cells. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1710–1716 Abstract : In this work, the charge transport properties of thin films made from a colloidal dispersion of polyaniline with poly(N‐vinylpyrrolidone) (PANI/PVP) are presented. The conductive film's contact and bulk resistance was studied on a device comprising coplanar gold electrodes and PANI/PVP film deposited via spin coating. The high stability of this dispersion with a large temperature range suggests application of this material for organic electronic devices.